Red Seaweed Gracilaria Arcuata in Cage Culture Area of Lawas, Sarawak - Othman, Muhammad Nur Arif; Hassan, Ruhana; Harith, Mohd Nasaruddin; Shah Ruddin Md Sah, Amir (Borneo Journal of Resource Science and Technology, 2016)
Red seaweed Gracilaria sp. is known as ‘Janggut Duyong’ by the local people of Sarawak. This macroalgae is well-distributed in both temperate and tropical seawaters. Gracilaria sp. could be processed to produce agar for industrial purposes whereas some people consumed it directly and become part of their daily diet. In terms of ecology, Gracilaria sp. is one of primary producer in the seawater and its presence can form habitats to support other aquatic organisms. Despite its socio-economic and ecological importance, little is known about Gracilaria sp. in Sarawak. Hence, this study is designed to: (i) determine the diversity and abundance of Gracilaria in cage culture of Lawas, Sarawak (ii) assess the water quality of the cage culture area where Gracilaria is found and (iii) determine other aquatic organisms that found within Gracilaria population. Three field samplings had been conducted from October 2013 to November 2014 at cage culture areas of Awat-Awat Village, Lawas, Sarawak. Only single species of Gracilaria was found namely Gracilaria arcuata. Besides G. arcuata, Acanthophora sp. and Padina sp. were also found but in small patches. In addition, five different groups of aquatic invertebrates were observed namely tunicates, bivalves, polychaetes, small crabs and brittle stars. The selected water quality parameters namely temperature, pH, dissolved oxygen, salinity, turbidity, total suspended solid, orthophosphate, silicate and chlorophyll a were significantly different (p= 0.000) during all the three field samplings except for nitrite (p= 0.588). However, the values recorded were within normal range of standard water quality for tropical estuarine area. Since healthy population of Gracilaria could be easily found here, therefore this area has the potential for future seaweed aquaculture.